A periodic adaptive current controller for torque ripple reduction in uncertain permanent magnet synchronous motor drives - Adiguzel, Fatih; Turker, Turker (SAGE PUBLICATIONS LTD, 2023)
This paper addresses an adaptive control approach to achieve high-performance response in phase currents and to minimize torque ripples in uncertain permanent magnet synchronous motor drives. In this manner, the electrical part of the permanent magnet synchronous motor drive is considered completely uncertain by taking the inherent characteristic of the parameters into account. A periodic adaptive controller is formulated in order to achieve the torque ripple reduction in the presence of the time-varying periodic uncertainties. In the sense that the periodic uncertainties appearing in permanent magnet synchronous motor drives change by the angular position, a change of the time variable is applied in the formulation of the proposed adaptive controller, and the stability analysis is conducted accordingly utilizing a Lyapunov-Krasovskii functional. Extensive numerical simulations are successfully performed for various operation points to validate the effectiveness of the proposed method.
Keywords: Periodic adaptive control; permanent magnet synchronous motor drive; torque ripple reduction; PREDICTIVE CURRENT CONTROL; TIME-VARYING PARAMETERS; DISTURBANCE OBSERVER; MINIMIZATION; MODEL; IPMSM; SUPPRESSION; MACHINES; VOLTAGE; Acoustics; Engineering; Mechanics